Deconstructing and Assessing Knowledge and Awareness in Public Health Research - Trevethan, Robert (Frontiers in Public Health, 2017)
When people’s knowledge and awareness are the subject of public health research, the meanings applied to the words knowledge and awareness are often unclear. Although frequently used interchangeably without that being problematic, these words sometimes appear to have different intended meanings but those meanings are not made explicit or, despite the meanings having been made explicit, they are not adhered to. It is necessary to overcome obscurities when knowledge and awareness are intended to represent different domains. This occurs when they are compared with each other; it also occurs when knowledge and awareness are assessed separately in relation to such variables as health behavior; physical, psychological, or socioeconomic statuses; gender; age; and ethnic backgrounds. For those particular research ventures, recommendations are made that knowledge be used to refer to information that is, to a greater or lesser extent, detailed and factual, and that awareness be associated with information that is personally relevant. Some suggestions are made, and issues are raised, about how the psychometric foundations for each of those two domains might be established prior to use in empirical research. Adopting the recommendations and suggestions made in this article provides opportunities for greater conceptual and empirical clarity and success.